Pengembangan Manfaat Bunga Kecombrang Menjadi Produk Selai Flora Di Kabupaten Tabanan - Adiguna Tumpuan; I Gusti Ayu Ari Agustini (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2021)
Jam is one of the most popular condiment in international culinary. Commonly, jam was produced using fruits as main ingredients, but few countries using flower as the ingredient for making jam. However, flower jam still not popular especially in Indonesia. Kecombrang (torch ginger) is one of native plant from Indonesia. Torch ginger flower is used by Indonesian for making chili paste, herbs for meat or fish dish, or cooked as vegetables stir fried. Torch ginger usage for sweet products is not commonly known by Indonesian. This study will develop torch ginger usage to become a jam. The purpose of this study are to find out whether jam made from torch ginger flowers can be well received through organoleptic tests so as to produce flora jam products made from torch ginger flowers. The method used in this research is descriptive quantitative. The result of this study are: 1) Torch ginger flower jam gets a good response from the aspects of color, aroma, and taste, but it needs development from the aspect of texture 2) Flora jam is highly potential to become local gif